Diversity of field weeds within Nadnidziański Landscape park, its conditions and protection - Fu-Dostatny, Denise (Plant Breeding and Seed Science, 2006)
In the years 1997 – 1999 a field research was carried out on distribution of field weeds of the Nadnidziański Landscape Park (50°18’–50°34’ N and 20°29’–20°49’ E). With the use of Braun-Blanquet method 149 phytosociological records were made. These records were made on fields with root and fodder cultivations. A soil investigation was carried out in order to determine the influence of soil on diversification of weed communities. The paper describes 4 associations occurring in the area, as well other truncated communities that cannot be assigned to any association due to absence of typical species. Lamio-Veronicetum politae is an association that occurs most frequently in the area of research although it is hardly ever observed in its typical from, as some of the typical species of the association are threatened by extinction. Permanent and abundant occurrence of such species as Chenopodium album or Galinsoga parviflora, which are dangerous weeds that compete strongly with other species of a small ecological scale, were also observed.